THE EFFECT OF SOCRATIC QUESTIONING ON READING COMPREHENSION ACHIEVEMENT OF EFL STUDENTS AT MUHAMMADIYAH UNIVERSITY OF PALEMBANG - Kurnia Saputri; Sri Yuliani; Endang Puji Astuti (Linguists : Journal of Linguistics and Language Teaching, 2026)
Socratic Questioning is a method of cooperative dialogue that employs disciplined, open-ended questions to stimulate critical thinking. This study aims to investigate: (1) the significant difference between EFL students’ reading comprehension before and after being taught using the Socratic Questioning method combined with critical reading strategies at Muhammadiyah University of Palembang, (2) the significant effect of the Socratic Questioning method on students’ reading comprehension achievement, and (3) the challenges faced by students in analyzing argumentative texts. This research employed a mixed-method approach, involving 30 EFL students selected through purposive sampling. Quantitative data were collected through reading comprehension tests and analyzed using a paired sample t-test, while qualitative data were obtained through in-depth interviews. The findings revealed that there was a statistically significant improvement in students’ reading comprehension after the implementation of the Socratic Questioning method, indicating a strong positive effect on students’ critical reading skills. Additionally, the qualitative results showed that students faced challenges related to identifying implicit arguments, evaluating evidence, and constructing logical interpretations of texts. This study contributes to filling the research gap in the limited application of Socratic Questioning in EFL higher education contexts in Indonesia, particularly in enhancing critical reading comprehension. In conclusion, the Socratic Questioning method is an effective pedagogical approach for improving students’ reading comprehension and critical thinking, although students require guided practice to overcome difficulties in analyzing argumentative texts.